Aircraft financing - Murphy, Rob (London, England : Bloomsbury Professional, 2021)
"Aircraft are mainly bought by two groups of buyers: 1. Airlines for their own use 2. Operating lessors for onward leasing to airlines Both groups of buyers require substantial external funding, both debt and equity, to accommodate these purchases. Historically five key sources have funded the aviation industry: 1. bank debt (secured and unsecured) 2. export credit agency guaranteed debt (secured) 3. capital markets (secured and unsecured bonds; equity and debt solutions) 4. internal cash flow generation 5. tax based leasing products This is the leading text providing guidance on all the funding options available, the best way to secure funding and how to ensure that robust legal structures framing the commercial deal are in place. The book is divided into four core sections: Part A: Market Context which sets the scene giving the user market context and an overview of aircraft financing Part B: Transaction structuring which looks at the credit, the asset, the legal structuring and tax drivers Part C: Core Products and Regional Markets (Brazil, Russia, India, China, France, Germany, Spain and Japan) Part D: Regulatory Matters including accounting developments Key updates for the new Fifth Edition include: - New chapters on: - The environment - Restructuring - Compliance - GATS (Global Aircrafts Trading Systems (GATS) - Full explanation and analysis of recent regulatory changes including changes brought about by Basel IV Due to the complexities involved in this area and the need to ensure that any commercial deal is legally sound Aircraft Financing is the essential reference tool for anyone involved in aircraft financing transactions."--
PART I: MARKET CONTEXT -- Chapter 1: Aviation Finance Introduction, Raymond Sisson -- Chapter 2: Overview of Aircraft Financing Markets, Jos Ǎbramovici -- Chapter 3: Aircraft Capital Markets, Zarrar Seghal and Madalyn Miller -- PART II: BUSINESS MODEL ? KEY ELEMENTS Chapter 4: Aircraft as Investments, Dick Forsberg -- Chapter 5: Legal Issues in Aircraft Finance, Rob Murphy -- Chapter 6: Cross-border Aircraft Leasing: Key taxation considerations, Joe O'Mara -- Chapter 7: In-House Valuation: Lessor perspectives, Randy Nightingale -- Chapter 8: Risk in Aviation Finance, Arthur Gaskin -- Chapter 9: Environmental Issues and the Aviation Industry, Rob Murphy and Fintan Kerins -- PART III: CORE PRODUCTS AND REGIONAL MARKETS Chapter 10: Export Credit Financing, Jeffrey Wool and William Coleman -- Chapter 11: Operating Leasing: Lessor perspectives, Rob Murphy -- Chapter 12: A Lessee's Guide to Aircraft Leasing, Michelle Johnson -- Chapter 13: Pre-delivery Payments Financing, Rob Murphy -- Chapter 14: Regional Markets 14(a) ? Brazil, Edward Sheard and Fabio Falkenburger -- 14(b) ? Russia, Mikhail Loktionov and Alexey Tokovinin -- 14(c) ? India, Marylou Bilawala and Tax-Gautam Nayak -- 14(d) ? China, Wang Ling and Wang Ning -- 14(e) ? Germany, Konrad Schott -- 14(f) ? Japan, Paul Greenwell and Akihiko Takamatsu -- Chapter 15: Islamic Finance, William Coleman -- Chapter 16: Insurance Considerations, Glen Brighton -- Chapter 17: Regional markets: Aircraft repossession, Melissa Whybrow -- Chapter 18: Global Aircraft Trading System (GATS), Dominic Pearson -- Chapter 19: Airline Restructurings, William Glaister, Philip Hertz, Jennifer DeMarco, Gabrielle Ruiz and Marisa Chan -- PART IV: REGULATORY MATTERS -- Chapter 20: The Regulatory Framework for Airline Operations, Alan Ryan -- Chapter 21: International Conventions Affecting Aircraft Financing Transactions, Laura Cunningham and Domhnall Breathnach -- Chapter 22: Basel III and IV: The regulatory framework, Brendan Wallace -- Chapter 23: Accounting Developments in Aircraft Finance, Killian Croke and Niamh Broder -- Chapter 24: Aircraft Financing: The compliance universe, Rob Murphy and Fintan Kerins.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Airlines -- Finance; Airlines -- Insurance; Aircraft leasing and renting; Law,Aerospace & air transport industries,Corporate finance,Aircraft: general interest; Electronic books